Réponses

Meilleure réponse !
  • x22
  • Modérateur Junior
2014-09-20T19:17:07+02:00
Salut!

A=6-z pour z=-4
=6-(-4)
=6+4
=10

B= 7+3y-(-4) pour y=2
=7+3x2-(-4)
=7+6+4
=13+4
=17

C= a-2b+c-2 pour a=-1; b=2,5; c=-1,5
=-1-2x2,5+(-1,5)-2
=-1-5+(-1,5)-2
=-6+(-3,5)
=-9,5

Voilà
2014-09-20T19:18:52+02:00

Calculer A pour z = -4

A = 6 - z

A = 6 - (-4)

A = 6 + 4

A = 10


Calculer B pour y = 2

B = 7 + 3y - (-4)

B = 7 + 3 x 2 + 4

B = 7 + 6 + 4

B = 17


Calculer C pour a = -1 ; b = 2,5 et c = -1,5

C = a - 2b + c - 2

C = (-1) - 2 x 2,5 + (-1,5) - 2

C = -1 - 5 - 1,5 - 2

C = -9,5


C'est pas -2 dans le B
merci mais x22 à répondu avant toi ! ^^
Et ?? :)